Bioharvesting and improvement of nano-silica yield from bagasse by irradiated Curvularia spicifera - Amira G. Zaki; Samah A. Yousef; Yasmeen A. Hasanien (BMC Microbiology, 2025)
Abstract Background Sugarcane bagasse is an organic waste material abundant in silica. Silica is a very significant inorganic substance that is widely employed in a variety of industrial applications.This study displays an eco-friendly and inexpensive biotransformation process producing silica nanoparticles (SNPs) using a primarily reported Curvularias picifera strain under solid-state fermentation (SSF) on bagasse as a starting material. The produced SNps were characterized by XRD, DLS, Zeta sizer, FT-IR, SEM, and TEM analyses. The silica bioleaching ability of C. spicifera was further amended by exposure to gamma irradiation at a dose of 750 Gy. The biotransformation process was additionally optimized by applying response surface methodology (RSM). Result According to screening experiments, the selected promising fungal isolate was identified as Curvularia spicifera AUMC 15532. The SNPs fabrication was significantly enhanced by gamma irradiation (optimal dose 750 Gy) and response surface methodology for the first time. The attained SNps’ size ranged from 30.6–130.4 nm depending on the biotransformation conditions employed in the statistical model, which is available for numerous applications. The XRD shows the amorphous nature of the fabricated SNPs, whereas the FTIR analysis revealed the three characteristic bands of SNPs. The outcomes of the response surface optimization demonstrated that the model exhibited an adequate degree of precision, as evidenced by the higher R2 value (0.9511) and adjusted R2 value (0.8940), which confirmed the model’s close correspondence with the experimental data. A gamma irradiation dose of 750 Gy was optimal for a significant increase in the silica bioleaching activity by C. spicifera fermented bagasse (71.4% increase compared to the non-irradiated strain).